Propuestas de política del consejo nacional de educación: banderas - Cardó Franco, Andrés (2010)
The National Board of Education presents some proposals of policies on education for the sustainability and life quality of all Peruvian citizens which have been denominated as BANDERAS. These should be implemented as soon as possible within the next five year period. lt considers that by orienting resources and efforts first on the following critica! nodes: childhood, rural education, performance evaluation and teacher training, education management, high education, education and production, fight against corruption, and budgeting, will be possible to break away from the routine which keep important sectors of population away from the success on education. This will continue laying the foundations to reach such an educational system in a short term like the ones of the economic and social most developed countries. In the present electoral context, it pretends to generate the reflection and enhance the political leaders' opinion about the urgent need of these topics to be attended by new regional governments and the next national government, adding willingness to incorporate them in the new work plans which will be implemented in the 2011-2016 term.